Preliminar toxicological assesement of Ruta graveolens, Origanum vulgare and Persea americana on the preimplantational mouse embryos - Benavides, V. (2000)
The growing interest in natural medicine makes it necessary to study plant properties as well as their possible secondary effects. In recent years the toxic effects of many medicinal plants on the preimplantational mouse embryo development have been studied. Many of them produce malformations and alterations in the embryonic development. Ruta graveolens "ruda", Origanum vulgare "oregano" and Persea americana "palta" are used in rural areas to menstrual colic and to provoke abortion (estrella, 1995). This study is aimed at assessing "in vivd'the effect of extracts of "oregano", "ruda" and "palta" to 20% on the morphology and growth of preimplantational mouse embryos.